2022
DOI: 10.24926/iip.v13i3.4956
|View full text |Cite
|
Sign up to set email alerts
|

Astropharmacy: Roles for the Pharmacist in Space

Abstract: Since disease is a natural aspect of life, human deep space missions will largely depend on preventing disease, diagnosis, and treatment. Pharmaceuticals are used to identify, treat, prevent, or cure illnesses, but they are unstable on Earth and even more so in space. What if the pharmacist could prepare small quantities of medicines in space, on site, as needed? The alteration in pharmacokinetic and pharmacodynamic (PK-PD) and pharmacogenomics with flying and medications will need to be customised for each pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Pharmacists play a critical role in ensuring the safe and effective use of medications [3] . However, a review by Shireen et al, [4] revealed that the practice of pharmacy in zero gravity environments presents unique challenges. Altered pharmacokinetics and pharmacodynamics [5] , compounding and storage difficulties, emergency medication management, and the lack of established guidelines and protocols are some of the key challenges pharmacists face [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists play a critical role in ensuring the safe and effective use of medications [3] . However, a review by Shireen et al, [4] revealed that the practice of pharmacy in zero gravity environments presents unique challenges. Altered pharmacokinetics and pharmacodynamics [5] , compounding and storage difficulties, emergency medication management, and the lack of established guidelines and protocols are some of the key challenges pharmacists face [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Bisher war der Beitrag von Pharmazeuten zur Gesundheit von Astronauten eher gering [34], es ist aber absehbar, dass die rasante Entwicklung der bemannten Raumfahrt hier für eine deutliche Steigerung sorgen wird [35]. Ähnliches dürfte für die Toxikologen gelten.…”
Section: Ausblickunclassified
“…With the increased interest in precision medicine in space, the commercialization of space, and the rise of synthetic biology [107][108][109], astropharmacy has recently emerged as a recognized field of specialization [110,111]. The goals of astropharmacy mirror those of pharmacy on Earth but with a specific focus on medication storage [112][113][114][115], access [114,115], use, and manufacturing beyond Earth [111,116].…”
Section: Genes Predicted To Be Altered In Space Are Predicted To Be A...mentioning
confidence: 99%
“…With the increased interest in precision medicine in space, the commercialization of space, and the rise of synthetic biology [107][108][109], astropharmacy has recently emerged as a recognized field of specialization [110,111]. The goals of astropharmacy mirror those of pharmacy on Earth but with a specific focus on medication storage [112][113][114][115], access [114,115], use, and manufacturing beyond Earth [111,116]. Current challenges include understanding how detrimental physiological changes in flight might be countered by existing medications, how medications may work differently in flight, and how to ensure our explorers receive the best possible outcome while minimizing side effects despite limited resources.…”
Section: Genes Predicted To Be Altered In Space Are Predicted To Be A...mentioning
confidence: 99%